2016
DOI: 10.1103/physreve.93.032116
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Gibbs ensemble in a nonintegrable system with an extensive number of local symmetries

Abstract: We numerically study the unitary time evolution of a nonintegrable model of hard-core bosons with an extensive number of local Z2 symmetries. We find that the expectation values of local observables in the stationary state are described better by the generalized Gibbs ensemble (GGE) than by the canonical ensemble. We also find that the eigenstate thermalization hypothesis fails for the entire spectrum, but holds true within each symmetry sector, which justifies the GGE. In contrast, if the model has only one g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…By contrast, for nonbipartite lattices, the winding numbers can be defined only modulo 2, and there are four sectors defined by a pair of Z 2 invariants [24,25]. Noting the effect of topological blocking on quench dynamics [26] and recalling the case of integrable models, where the extensive number of conserved quantities invalidates ETH, it is natural to ask whether the existence of these topological invariants will influence ETH in the QDM [18].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, for nonbipartite lattices, the winding numbers can be defined only modulo 2, and there are four sectors defined by a pair of Z 2 invariants [24,25]. Noting the effect of topological blocking on quench dynamics [26] and recalling the case of integrable models, where the extensive number of conserved quantities invalidates ETH, it is natural to ask whether the existence of these topological invariants will influence ETH in the QDM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all known examples not satisfying the ETH violates at least one of (i)-(iii). Integrable systems [24,30,41,42] and systems with local symmetries [47] violate (ii), and systems with Anderson localization [48,49] or many-body localization [50,51] violate (i). It is noteworthy that these examples do not thermalize.…”
mentioning
confidence: 99%
“…Counterexamples are the driven Rabi model56 or a non-integrable model of hard-core bosons on connected triangular lattices57. For the latter one it has been shown that the applicability of the CGE to the stationary state depends on the symmetries in the system: In case of an extensive number of local symmetries the GGE has to be applied rather than the CGE.…”
mentioning
confidence: 99%